A CASE OF DISTAL RENAL TUBULAR ACIDOSIS PRESENTING AS BONE AND JOINT PAINS - ., Muhammad Afzal; ., Shabbir Hussain; Qureshi, Shoukat Mehmood (Pakistan Armed Forces Medical Journal, 2011)
A 13 years old girl presented with generalized bone and joint pains for last five years. Complaints had progressed to difficulty in walking. Now she was severly incapacitated, non ambulatory and had to discontinue schooling a year ago. She was born of consanguineous marriage and had seven siblings. One elder brother died at age of 16years due to renal failure. Her height and weight were at 50th percentile. There was no swelling or deformities of joints, however she had generalized bone tenderness. Power was normal in all limbs. She had severe pain on walking and was restricted to bed. Rest of general and physical examination was unremarkable. There were no features suggestive of liver disease, malabsorption, Sjogren’s syndrome, systemic lupus erythematosis, rheumatoid arthritis. She was receiving multiple analgesics and vitamin supplements but without relief. Biochemical and urine examination profile is summarized in table.